PREVENTION OF CORRUPTION WITHIN STUDENT ORGANIZATIONS - Amalia, Siti Dita Nurul; Muflihah, Muflihah; Bainah, Atiqoh Nur; Azzahra, Siti; Ahyar, Zaky Khairul; Hardiansyah, Muhammad Agus (Universitas Tanjungpura, 2023)
This study has two objectives, the first is to analyze and evaluate the factors that influence students' corruption intentions in managing anti-corruption organization funds, and the second to identify and analyze opportunities. corruption in the implementation of student activities. The problem is, that the students know that corruption has occurred but cannot report it because they are meeting with friends. The purpose of this research is to fill the research gap, namely. examines the phenomenon of student decision-making in reporting corruption in student financial management through a whistleblowing mechanism using the theory of planned behavior and a framework of moral standards. This research uses a qualitative case study. The data collection method is a literature search. Content and thematic analysis techniques are used in the analytical techniques. The results showed that the factors that influence the intention of organizational members to report corruption in the management of organizational assets include: Attitudes, subjective norms, and perceptions of behavioral control are not the dominant factors, while moral norms are the dominant factors. by establishing the intention of student body members to take action to report corruption. The whistleblowing mechanism is implemented using witness reports (whistleblowing).